Thompson, John B., Merchants of Culture: The Publishing Business in the Twenty-First Century, Cambridge: Polity, 2010 - McGrath, Laura (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2026)
John B. Thompson’s Merchants of Culture is routinely cited as the most in-depth and influential examination of the US literary publishing industry in the twenty-first century. This article examines Thompson’s research and impact nearly 15 years after its initial publication. It considers its uses for researchers at present—both Thompson’s thoroughness, and areas of oversight. Considering Merchants of Culture from 2026, this article surfaces many of the questions that Thompson raised that are still to be addressed by researchers in the coming years.